DESIGN OF WIRELESS SENSOR NETWORKS BASED ON 5G AND IOT TECHNOLOGIES IN HIGHER EDUCATION INSTITUTIONS AND IMPROVEMENT OF DATA CYBERSECURITY ASSURANCE MECHANISMS - Saparov Umidjon Ali o’g’li,; Yorqinbek Ergashov Abduazizovich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
This article examines the issues of developing wireless sensor networks based on 5G and IoT technologies in higher education institutions and ensuring their efficient operation. In addition, the requirements for creating a digital smart campus environment necessary for managing data processes and network infrastructure are identified in order to establish a 5G/IoT network for scientific research purposes. The assessment of these requirements was carried out based on an existing campus network.Furthermore, the mechanisms for ensuring the cybersecurity of data transmitted through wireless sensor networks are analyzed.The study explores modern methods of designing sensor networks, network architecture, as well as cryptographic and authentication techniques for data protection.The obtained results contribute to the development of smart campus systems in higher education institutions, ensuring secure data transmission, and improving network stability. The most promising innovative solutions can later be implemented at both national and international levels. In addition, the locally managed experimental 5G/IoT network infrastructure established within the campus can serve as a basis for developing new regulatory approaches and business models in response to expected changes in the future telecommunications market.